HCV/HTLV coinfection: Does HTLV‐1 interfere in the natural history of HCV‐related diseases?. Issue 11 (22nd April 2016) - Silva, Marcelo Costa; Silva, Carolina Alves Costa; Machado, Gustavo Uzêda; Atta, Ajax; M. Freire, Songeli; Carvalho, Edgar; Schinoni, Maria Isabel; Paraná, Raymundo
Abstract : Hepatitis C virus (HCV) and human T‐lymphotropic virus type 1 (HTLV‐1) coinfection occurs in many regions. However, few studies have focused on the natural history of HCV‐induced liver disease in coinfected patients. To describe the clinical, epidemiological, and histopathological aspects of HTLV‐1/HCV coinfection in Brazil. A cross‐sectional study with 23 patients coinfected with HCV/HTLV. The control groups consisted of 21 patients monoinfected with HCV and 20 patients monoinfected with HTLV‐1. The cytokine profiles (Th1 and Th2 cell responses), clinical, laboratory features, and histopathological aspects were examined. The control group for cytokine analysis validation consisted of patients monoinfected with HTLV, and a fourth group consisted of healthy blood donors. No anthropometric differences present between the three infected groups. We observed higher serum concentrations of IFN‐γ in patients coinfected with HCV/HTLV‐1 than those in HCV monoinfected patients. The HCV/HTLV‐1 coinfected group also exhibited a higher degree of liver steatosis than the HCV monoinfected patients. Results suggest that HCV/HTLV‐1 coinfection may result in a different pattern of HCV infection due to the immunologic disorders likely associated with HTLV‐1, but there is no clear evidence of the HTLV role in the natural history of HCV infection. J. Med. Virol. 88:1967–1972, 2016 . © 2016 Wiley Periodicals, Inc.